Sweet Poison: Syrup Drugs and the Imperative of Consumer Protection against Acute Renal Failure - Suwandono, Agus; Yuanitasari, Deviana (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2023)
Efforts to handle cases of acute kidney failure in children still cause problems related to the accountability of pharmaceutical business actors and legal protection for consumers and the community. This research uses a normative juridical approach with descriptive and analytical specifications. BPOM has instructed the recall of all syrup medications from circulation that contain EG and DEG, totaling around 73 syrup medications from 5 pharmaceutical industries. The purpose of writing this article is to formulate the responsibility of those involved in the circulation of children's syrup medications that cause acute kidney disorders from a consumer protection perspective and to formulate legal protection for consumers regarding the circulation of children's syrup medications from a consumer protection perspective. The results showed that pharmaceutical business actors in the consumer protection perspective could be held criminally, civilly, and administratively held accountable simultaneously. Legal protection for consumers can be prevented by adequate supervision, especially regarding drugs circulating in the community. As for repressively withdrawing the circulation of syrup drugs containing Ethylene Glycol and Diethylene Glycol that exceed the safe threshold and carrying out law enforcement against pharmaceutical business actors who violate the provisions of laws and regulations. The government should be proactive and facilitate consumers who are victims of acute kidney failure to obtain their rights as consumers.